Adequate access to healthcare and added life expectancy among older adults in China - Hao, Lisha (BMC Geriatr, 2020)
BACKGROUND: Adequate access to healthcare is associated with lower risks of mortality at older ages. However, it is largely unknown how many more years of life can be attributed to having adequate access to healthcare compared with having inadequate access to healthcare. METHOD: A nationwide longitudinal survey of 27,794 older adults aged 65+ in mainland China from 2002 to 2014 was used for analysis. Multivariate hazard models and life table techniques were used to estimate differences in life expectancy associated with self-reported access to healthcare (adequate vs. inadequate). The findings were assessed after adjusting for a wide range of demographic factors, socioeconomic status, family/social support, health practices, and health conditions. RESULTS: At age 65, adequate access to healthcare increased life expectancy by approximately 2.0–2.5 years in men and women and across urban-rural areas compared with those who reported inadequate access to healthcare. At age 85, the corresponding increase in life expectancy was 1.0–1.2 years. After adjustment for multiple confounding factors, the increase in life expectancy was reduced to approximately 1.1–1.5 years at age 65 and 0.6–0.8 years at age 85. In women, the net increase in life expectancy attributable to adequate access to healthcare was 6 and 8% at ages 65 and 85, respectively. In men, the net increases in life expectancy were generally greater (10 and 14%) and consistent after covariate adjustments. In contrast, the increase in life expectancy was slightly lower in rural areas (2.0 years at age 65 and 1.0 years at age 85) than in urban areas (2.1 years at age 65 and 1.1 years age 85) when no confounding factors were taken into account. However, the increase in life expectancy was greater in rural areas (1.0 years at age 65 and 0.6 years at age 85) than in urban areas (0.4 years at age 65 and 0.2 years at age 85) after accounting for socioeconomic and other factors. CONCLUSIONS: Adequate access to healthcare was associated with longer life expectancy among older adults in China. These findings have important implications for efforts to improve access to healthcare among older populations in China.